KADER MANIS (KADER POSYANDU TANGGAP MANAJEMEN DIABETES MELITUS) - Dudella Desnani Firman Yasin; Ashar Abilowo; Pebri Emilda Nurriska (Universitas Kadiri, 2026)
This community service activity focuses on empowering posyandu cadres through the Kader Manis program (Kader Posyandu Tanggap Manajemen Diabetes Melitus) to improve knowledge and early detection capabilities related to diabetes mellitus (DM). The objective of this program was to increase cadres’ understanding of DM risk factors, symptoms, and management principles through structured health education, discussions, and evaluation using pre-test and post-test. The method used included need assessment, participatory planning, implementation of education using visual media, and evaluation of knowledge improvement. The results showed a significant increase in cadres’ knowledge, with the average score rising from 72.50 to 87.50. This empowerment strengthened cadres’ capacity to provide DM-related screening, education, and community assistance. The program is expected to support early prevention efforts and strengthen community-based health promotion.